2022
DOI: 10.1016/j.molmet.2021.101414
|View full text |Cite
|
Sign up to set email alerts
|

Increased glycolysis affects β-cell function and identity in aging and diabetes

Abstract: Objective Age is a risk factor for type 2 diabetes (T2D). We aimed to elucidate whether β-cell glucose metabolism is altered with aging and contributes to T2D. Methods We used senescence-accelerated mice (SAM), C57BL/6J (B6) mice, and ob / ob mice as aging models. As a diabetes model, we used db / db mice. The glucose responsiveness of insulin secretion and the [U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 97 publications
0
16
0
1
Order By: Relevance
“…S2A,B ; Supplementary file 2). While these data do not address the reasons for the sex-biased risk of T2D, and could reflect differences in medication [ [62] , [63] , [64] , [65] ], age [ 12 , 16 , [66] , [67] , [68] ], and body mass index [ 15 , 68 ], our data suggest biological sex influences β cell gene expression in T2D.
Figure 1 Sex differences in human islet transcriptomic and functional responses in type 2 diabetes.
…”
Section: Resultsmentioning
confidence: 92%
“…S2A,B ; Supplementary file 2). While these data do not address the reasons for the sex-biased risk of T2D, and could reflect differences in medication [ [62] , [63] , [64] , [65] ], age [ 12 , 16 , [66] , [67] , [68] ], and body mass index [ 15 , 68 ], our data suggest biological sex influences β cell gene expression in T2D.
Figure 1 Sex differences in human islet transcriptomic and functional responses in type 2 diabetes.
…”
Section: Resultsmentioning
confidence: 92%
“…By examining β cell [Ca 2+ ] and electrical communication during aging in mouse and human islets, Westacott et al (2017) found that there was a decline in the coordination of [Ca 2+ ] dynamics, gap junction coupling, and insulin secretion dynamics with age, indicating an age-related decay in stimulus-secretion coupling in β cell. In addition, aged mouse islets show increased glycolysis and altered cytosolic NAD metabolism, affecting β cell function and identity, similar to that seen in diabetic islets (Murao et al, 2022). Metabolite profiling identified 1,5-AG, 5′-methylthioadenosine (5′-MTA), X-11315 as potential biomarkers of pancreatic aging and T2D in human serum, saliva, and urine samples (Mook-Kanamori et al, 2017;Pramodkumar et al, 2016;Wang et al, 2017e;Zhang et al, 2021c).…”
Section: Molecular Changesmentioning
confidence: 83%
“…[38] Similarly, in the human pancreas, PDX1 expression is markedly downregulated with aging. [39] Remarkably, a single-cell RNA-seq analysis revealed that the number of bihormonal cells that simultaneously expressed both insulin and glucagon mRNA increased with age, and the presence of such transcriptionally noisy cells suggests a fate drift between α- and β-cells in the aging pancreas, resulting in a loss of β-cell identity and function. Likewise, these transcriptionally noisy cells associated with aging are also observed in pancreatic islet cells from cynomolgus monkeys.…”
Section: Mechanisms Leading To β-Cell Failurementioning
confidence: 99%